The advantages of TCM in the treatment of gynecologic malignancies - Jiang, Wei; Yuan, Jinghua; Zhang, Xinling; Zhu, Shuying; Li, Xiaoping (Frontiers in Oncology, 2025)
Gynecological malignancies are characterized by high morbidity and mortality rates. With the development of society, the status of women continues to improve, yet the social pressure they bear increases daily. The incidence rate of gynecological malignancies in the female population has always remained at a high level, and the age of onset has shown a trend of getting younger. Common gynecological malignancies include cervical cancer, ovarian cancer, and endometrial cancer. Alarmingly, over 70% of patients are diagnosed at an advanced stage. This disease is mainly treated through surgery and radiotherapy, but there is still a relatively high recurrence rate after treatment. In recent years, with the development of traditional Chinese medicine (TCM), the advantages of TCM in the treatment of gynecological malignancies have gradually emerged. The entry of TCM into the treatment of Gynecologic malignancies is a tumor treatment method that has received close attention from the international medical community in recent times. TCM can be used throughout the whole process of tumor treatment. Combining Western medicine at different stages of the tumor, or giving different Chinese medicines alone, can minimize the toxic side effects of Western medicine treatment, alleviate symptoms, prolong survival and improve the quality of survival. Therefore, combining traditional Chinese medicine to provide individualized treatment for patients may become a better approach to cancer treatment. This article reviews the status and important role of TCM in gynecological malignancies in the hope of exploring new treatment modalities to mitigate the impact of gynecological malignancies on women’s health.